Is There Any MRI Pattern That Discriminates Female From Male Migraine Patients? - Maleki, Nasim; Androulakis, Xiao Michelle (Frontiers in Neurology, 2019)
There has been accumulating evidence on sex disparity in incidence, prevalence, symptomology and burden of migraine. Several neuroimaging studies on migraine patients attempted to unravel the mechanisms of the disease, yet very few of them examined the sex-related differences. Here, we will first discuss some of the reported neuroimaging patterns that discriminate females from males in migraine. We will then re-examine the salient neuroimaging findings in migraine and discuss them in relation to sex-related influences. Finally, we will discuss some of the intriguing recent data suggesting the presence of sex-specific traits in migraineurs. These findings may have potential implications for future neuroimaging studies to identify underlying correlating patterns in the brain to 1) explain the neural basis for higher prevalence of migraine in women, and 2) better understand migraine-specific changes during different stages of life in both men and women.